The evaluation of sorghum dried distiller's grains with solubles in nursery pig diets, on finishing pig performance and meat quality, and on lactating sow performance. - Sotak, Kelly Marie (Kansas State University, 2012)
Five experiments were conducted to determine the effects of sorghum dried distiller’s grains with solubles (DDGS) on nursery pig performance, finishing pig performance and meat quality, and lactating sow and litter performance. Experiment 1 established a nutrient database and evaluated the quality and consistency of five ethanol plants in the Western Plains region. Each sample was analyzed for AA, DM, CP, crude fiber, crude fat, ash, NDF, ADF, Ca, P, trace minerals, GE, and starch. In addition, DE, ME, and NE were calculated. Experiments 2 and 3 evaluated the effects of sorghum DDGS on nursery pig performance. In Exp. 2, pigs fed sorghum- or corn-based diets performed similarly; however, as sorghum DDGS increased ADG decreased (linear, P < 0.01). A DDGS×grain source interaction (quadratic, P = 0.03) was observed for G:F. In corn-based diets, G:F was identical for pigs fed 0 to 30% DDGS, but worsened in pigs fed 45% DDGS. In sorghum-based diets, G:F was best for those fed 0% DDGS, but worsened at higher levels. In Exp. 3, pigs fed corn- or sorghum-based diets performed similarly; however, pigs fed DDGS gained less (P < 0.03) than those fed basal diets. Experiment 4 evaluated the effects of sorghum DDGS in sorghum- or corn-based diets on finishing pig growth performance, carcass characteristics, and fat quality. Increasing sorghum DDGS reduced (linear; P < 0.01) ADG and increased (linear; P < 0.01) backfat IV. Pigs fed the sorghum-based diet with 30% sorghum DDGS had decreased backfat IV (P < 0.01) than those fed the sorghum-based diet with corn DDGS. Experiment 5 evaluated the effects of sorghum DDGS on lactating sow and litter performance. Overall, ADFI increased in corn-based diets when DDGS were added, but decreased in sorghum-based diets resulting in a tendency (P < 0.08) for a DDGS × grain source interaction. Pig weaning weights were lower (P < 0.06) for sows fed diets containing DDGS compared with those fed the basal diets. Adding sorghum DDGS reduced pig performance, and sow lactation performance; therefore, its inclusion in swine diets needs to be evaluated on an income over feed cost basis.
Keywords: Sorghum; Dried distiller's grains; Solubles; Animal Sciences (0475)